2022
DOI: 10.1021/acs.cgd.2c00183
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Organic–Inorganic Hybrid Materials with Dielectric Switching and Photoluminescence Properties

Abstract: Layered 2D organic−inorganic halide perovskites have attracted comprehensive scientific attention due to their excellent dielectric, ferroelectric, and photophysical properties. However, most of the reported crystal compounds only possess a single performance. Here, we report two new layered 2D organic− inorganic halide perovskites: [BA-PbBr 4 ] (Prv-1) and [MACH-PbI 4 ] (Prv-2) (BA = 1-butylamine, MACH = cyclohexanemethylamine). Both compounds (with crystal structures) show switchable phase transitions at 390… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 64 publications
0
16
2
Order By: Relevance
“…Comparing the BTYA solution with the PbBr 2 /BTYA solution, we find the peaks of the BTYA solution at 398, 797, 1299, and 1441 cm –1 shift to higher vibrational frequencies in the PbBr 2 /BTYA solution. These peaks are ascribed to C–N torsion, NH 2 torsion, C–H 2 twist, and C–H 2 bending, respectively. , This shift in the PbBr 2 /BTYA solution suggests the interaction between the BTYA ligand and PbBr 2 , likely through the amine group …”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Comparing the BTYA solution with the PbBr 2 /BTYA solution, we find the peaks of the BTYA solution at 398, 797, 1299, and 1441 cm –1 shift to higher vibrational frequencies in the PbBr 2 /BTYA solution. These peaks are ascribed to C–N torsion, NH 2 torsion, C–H 2 twist, and C–H 2 bending, respectively. , This shift in the PbBr 2 /BTYA solution suggests the interaction between the BTYA ligand and PbBr 2 , likely through the amine group …”
mentioning
confidence: 93%
“…27,28 This shift in the PbBr 2 /BTYA solution suggests the interaction between the BTYA ligand and PbBr 2 , likely through the amine group. 29 The PbBr 2 -BTYA MCs were characterized in the solid state in the low-Raman vibrational frequency region to determine the vibrational phonon modes of MCs. Figure 4b shows several vibrational peaks at low frequencies on different thicknesses of solid films.…”
mentioning
confidence: 99%
“…32−42 For example, Chen et al reported a new layered perovskite, (4-fluorophenethylaminium) 2 [CuCl 4 ], which shows aboveroom-temperature ferroelasticity, reversible thermochromism, semiconductivity, and low-temperature ferromagnetic ordering. 43 Fu et al reported an organic−inorganic hybrid perovskite, [(BA) 2 −PbI 4 ] (compound 1, BA = n-butylamine), which can achieve ideal optical and dielectric switching performance simultaneously. 44 Among these reports, the phase transition is mainly caused by the order−disorder arrangement of organic ammonium cations, which provide a potential strategy to find new multifunctional OIHMs by adjusting organic ammonium cations.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For example, Chen et al reported a new layered perovskite, (4-fluorophenethylaminium) 2 [CuCl 4 ], which shows above-room-temperature ferroelasticity, reversible thermochromism, semiconductivity, and low-temperature ferromagnetic ordering . Fu et al reported an organic–inorganic hybrid perovskite, [(BA) 2 –PbI 4 ] (compound 1, BA = n -butylamine), which can achieve ideal optical and dielectric switching performance simultaneously .…”
Section: Introductionmentioning
confidence: 99%
“…Organic–inorganic hybrid materials have many benefits: inexpensive raw materials, easy synthesis, and structural flexibility. Due to their exceptional qualities, these materials have received a lot of attention, including band gap adjustability, phase transition characteristics, and nonlinear optical switching characteristics. The inorganic and organic parts could compose ″host cages″, which could easily result in phase transition accompanied with abrupt changes in physical properties close to the phase transition point. The low-dimensional compounds have unprecedented structural flexibility and adjustability in photoelectric properties compared with 3-D hybrid materials. For instance, Zhang’s group reported a 0-D organic–inorganic hybrid material that underwent multistep reversible phase transition …”
Section: Introductionmentioning
confidence: 99%